2018
DOI: 10.24326/asphc.2018.6.3
|View full text |Cite
|
Sign up to set email alerts
|

DOES PRESERVATION MODIFY THE ESSENTIAL OIL CONTENT AND CHEMICAL COMPOSITION OF LEAF CELERY (Apium graveolens L. var. secalinum Alef.)?

Abstract: Preservation of spice plants usually leads to changes in the structure and content of biologically active substances. The present study determined the effect of lyophilization and convection drying on the content and chemical composition of the essential oil from leaves of two leaf celery cultivars. Compared to lyophilization, convection drying allows a larger amount of essential oil to be retained in leaves of leaf celery (respectively by 0.48 and 0.21%). The oil obtained from the material preserved using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The application of organic manure encourages the proliferation of soil microbes and inducing root lateral hence increases the biomass of the root system which following by carbon content accumulation [13]. Rhizobacteria simultaneously involves in various stages of plant growth, such as germination until harvest phase [14] The cultivation of aromatic plants with organic fertilizers can improve soil health and determine factor for quality of essential oils [15]. Rhizobacteria was added to roots contained bacteria and fungi, there are Rhizobium sp., Lactobacillus sp., Trichoderma sp., Aspergillus sp., and Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of organic manure encourages the proliferation of soil microbes and inducing root lateral hence increases the biomass of the root system which following by carbon content accumulation [13]. Rhizobacteria simultaneously involves in various stages of plant growth, such as germination until harvest phase [14] The cultivation of aromatic plants with organic fertilizers can improve soil health and determine factor for quality of essential oils [15]. Rhizobacteria was added to roots contained bacteria and fungi, there are Rhizobium sp., Lactobacillus sp., Trichoderma sp., Aspergillus sp., and Penicillium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our research, we also found the same results, fresh weight, dry weight, and oil content increased after PGPR added compared without PGPR. Nurzynska-Wierdak [15], states the availability of essential nutrients N, P, K, Ca, and Mg effect on composition of essential oils particular like citronellal, citronellol, and geraniol. The role of rhizobacteria support the dissolution of nutrients, especially Nitrogen and Phosphorus in the soil thus it impacts on growth and induction of oil components in aromatic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Fertilization is also a significant factor modifying some EO components in aromatic plants. Nurzyńska‐Wierdak 31 (and refences therein) reported on the effect of macro‐ and microelements as nutrients on aromatic plant metabolism. Studies on the effect of N (inorganic and organic), P and other minerals (S, Zn, Fe, Ca, etc.)…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the effect of N (inorganic and organic), P and other minerals (S, Zn, Fe, Ca, etc.) on EO yield and composition of many aromatic plants were summarized and discussed; Nitrogen, in the form of organic fertilizer, increased the content of linalool and borneol in Ocimum basilicum EO, simultaneously decreasing methyl chavicol and 1,8‐cineole 31 . Moreover, increasing the NPK rate in chamomile cultivation led to an increase in EO content and yield, and in the amount of germacrene D and α‐bisabolol in ΕΟ.…”
Section: Introductionmentioning
confidence: 99%
“…Among abiotic factors, soil fertility plays a significant role in developing quality medicinal plants ( Verma and Shukla, 2015 ; Soltanbeigi, 2020 ). The quality and yield of herbal plants can be increased effectively by fertilization as amino acids and enzymes involved in the biosynthesis of numerous essential oil compounds are, in turn, synthesized by the plant using nitrogen (N), phosphorus (P), and potassium (K) primarily ( Nurzynska-Wierdak, 2013 ).…”
Section: Introductionmentioning
confidence: 99%